Undergraduate and Graduate Students’ Beliefs about Dyslexia: Implications for Initial Foreign Language Teacher Education - Alma Žero; Karmen Pižorn (Center for Educational Policy Studies Journal)
The purpose of this study was to explore undergraduate and graduate students’ beliefs about dyslexia at the Department of English Language and Literature of the University of Sarajevo in Bosnia and Herzegovina and subsequent implications for initial foreign language teacher education. The study follows a convergent parallel mixed methods design. A questionnaire was used to gather quantitative data on students’ beliefs about dyslexia and to consider potential variances at different levels of study. A group interview was used to gather qualitative findings for further consideration in initial teacher education on dyslexia and other specific learning difficulties. The findings have shown that both undergraduate and graduate students have an almost equal number of misconceptions about dyslexia, with the majority (96.03%) affirming that they need more training in teaching students with dyslexia or other specific learning difficulties. Furthermore, the study follows an emergent framework with reference to three main themes: (1) teacher beliefs and attitudes, (2) teaching practices, and (3) teacher preparation, which also reflect the main areas of undergraduate and graduate students’ concerns in teaching students with dyslexia and other specific learning difficulties.